Anti-Tumor Activity of AZD4547 Against NTRK1 Fusion Positive Cancer Cells Through Inhibition of NTRKs - Cho, Hanna; Kim, Namkyoung; Murakami, Takashi; Sim, Taebo (Frontiers in Oncology, 2021)
Inhibitors of tropomyosin-related kinases (TRKs) display remarkable outcomes in the regression of cancers harboring the Neurotrophin Receptors Tyrosine Kinase (NTRK) fusion gene. As a result, TRKs have become attractive targets in anti-cancer drug discovery programs. Here, we demonstrate that AZD4547, a highly potent and selective inhibitor of fibroblast growth factor receptor (FGFR), displays anti-tumor activity against KM12 harboring the TPM3-NTRK1 fusion gene associated with its direct inhibition of TRKs. The results of profiling, using a 64-member in-house cancer cell panel, show that AZD4547 displays anti-proliferation activity against KM12 with a GI50 of 100 nM. In vitro biochemical assays reveal that AZD4547 has IC50 values of 18.7, 22.6 and 2.9 nM against TRKA, B and C, respectively. In a cellular context, AZD4547 blocks auto-phosphorylation of TRKs and phosphorylation of its downstream molecules including PLC-gamma and AKT in a dose dependent manner. Also, AZD4547 at 0.1 μM concentration downregulates expression of MAPK target genes (DUSP6, CCND1 and ETV1) as well as the E2F pathway. Furthermore, AZD4547 induces G0/G1 arrest and apoptosis, and suppresses anchorage independent growth of KM12. Oral administration of 40 mpk AZD4547 dramatically delays tumor growth in a KM12 implemented xenograft model, without promoting body weight changes. The capability of AZD4547 to inhibit TRKA, TRKB and clinically relevant mutants (TRKA G595R, G667S, G667C and G667A) was also evaluated using Ba/F3 cells harboring the ETV6-NTRKs fusion gene. The combined observations demonstrate the potential application of AZD4547 for treatment of NTRK fusion driven cancers.